ANALISIS INTENSITAS CAHAYA DI LABORATORIUM PT X METODE SNI 7062:2019 - Syamsi, Wuri Arianty; Setianto, Nasrul; Saepuloh, Asep; Suyono, Annisa Maharani (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
The health of the physical work environment is a crucial factor that influences employee productivity, comfort and well-being in the workplace. A healthy work environment not only improves work efficiency but also plays a role in reducing the risk of disease and injury. Physical aspects of the work environment, such as lighting, temperature, noise, air quality, and ergonomics, have a direct impact on the physical and mental condition of employees. Working environmental conditions such as heat, noise, lighting, temperature, humidity, vibration and others need to be studied to prevent mental and physical strain on employees. With a good understanding of the health of the work environment, companies can take the right steps to create a healthier and more productive work environment